International Geological Correlation Programme (IGCP) Project 502: Global Comparison of Volcanic-hosted Massive Sulphide (VMS) Districts: The controls on distribution and timing of VMS deposits - Rodney Allen (Canadian Institute of Mining, Metallurgy and Petroleum, 2005)
Background: Development of the Project ?European GEODE collaboration 1999: considers possible projects, including a VMS project, to continue after GEODE ?GEODE-CODES-Canada collaboration 1999: Questionaire, database ?Workshop at CODES 2000: project theme and strategy selected ?GEORANGE (Sweden-EU) 2001 supports development of Global VMS Project: interest from 12 nations ?Skellefte VMS Project set up as Sweden?s component of Global VMS, 2002; other projects in Spain, Canada collaborate ?Low metal prices ---> little funding from mining industry 2001-2003, change in strategy ?IGCP/UNESCO support 2004: enlargement to over 20 nations